Multiparametric MR imaging of Parkinsonisms at 3 tesla: Its role in the differentiation of idiopathic Parkinson's disease versus atypical Parkinsonian disorders. Issue 109 (December 2018) - Calloni, S.F.; Conte, G.; Sbaraini, S.; Cilia, R.; Contarino, V.E.; Avignone, S.; Sacilotto, G.; Pezzoli, G.; Triulzi, F.M.; Scola, E.
Abstract: Objectives: The Nigrosome-1 and putaminal hypointensity depicted on susceptibility-weighted imaging (SWI), and midbrain atrophy assessed on T1-weighted are some of the most common radiological parameters to diagnose Parkinsonism at Magnetic Resonance (MR) imaging. Our aim is to assess the feasibility of these signs in the differentiation of Idiopathic Parkinson's disease (IPD) patients versus disease (DC) and healthy controls (HC) and in the assessment of the Atypical Progressive Parkinsonisms (APPs). Methods: Presence or loss of the Nigrosome-1 was assessed retrospectively on multiple-echo SWI obtained on a 3 T scan by two neuroradiologists. Results were compared with the 123I-FP-CIT SPECT images. Morphologic diagnostic features suggestive of APPs such as midbrain atrophy and putaminal hypointensity were evaluated by qualitative scores. The midbrain and putaminal scores were summed (combined score) and then added to the Nigrosome-1 score (global score). Results: The study included 126 patients with IPD (n = 56), APPs patients (n = 30; 18 PSP, 3 MSA-C, 9 MSA-P), 16 DC and 24 HC. Sensitivity and specificity of the Nigrosome-1 in discriminating IPD from controls were 96, 43% and 85.00%, APPs from controls were 100% and 85%, IPD from APPs were 96, 43% and 0% respectively. Combined score for midbrain atrophy and putaminal hypointensity resulted in the most accurate for distinguishing APPs from IPD with a value of ≥ 2 (AUC = 0.98). Conclusion: Nigrosome-1 is a valid tool to differentiate IPD-APPs from controls. The combined score of midbrain atrophy and putaminal hypointensity represents a valid diagnostic pointer in the differential diagnosis of APPs from IPD.